Message of the Holy and Great Council of the Orthodox Church (The Greek Orthodox theological review, 2017)
Greek Orthodox Theological Review 62:3-4 2017 59 Message of the Holy and Great Council of the Orthodox Church To the Orthodox people and to all people of good will. *** Apart from the specific topics about which it decided, the Holy and Great Council notes in brief the following important contemporary issues: 7) In regard to the matter of the relations between Christian faith and the natural sciences, the Orthodox Church avoids 63 Message of the Holy and Great Council placing scientific investigation under tutelage and does not adopt a position on every scientific question. The re-evangelization of God's people in modern, secularized societies and the evangelization of those who have still not come to know Christ remain an unceasing obligation for the Church.